Introduction - Flotmann-Scholz, Christina; Lienen, Anna (Victorian Ideologies in Contemporary British Cultures)

Money Makes the Reviewer Go Round – Ambivalent Effects of Online Review Elicitation in B2B Markets - Neumann, Jürgen; Gutt, Dominik (Proceedings of the 25th Americas Conference on Information Systems (AMCIS))

When does Local Status Matter? – The Relationship between Reviewer Location and Perceived Usefulness of Online Reviews - Neumann, Jürgen; Gutt, Dominik; Görzen, Thomas; Kundisch, Dennis (Proceedings of the 25th Americas Conference on Information Systems (AMCIS))

Reviewing the Vendor or the Product – Analyzing Vendor versus Product Representation in B2B Review Systems - Poniatowski, Martin; Neumann, Jürgen; Kundisch, Dennis (Proceedings of the 25th Americas Conference on Information Systems (AMCIS))

Organizing Their Thoughts – How Online Review Templates Affect the Review Text - Poniatowski, Martin; Neumann, Jürgen; Görzen, Thomas; Kundisch, Dennis (Proceedings of the 27th European Conference on Information Systems (ECIS))

The Virtues of Anonymity - An Empirical Investigation of the Relationship between B2B Online Ratings and Reviewer Self-Disclosure - Gutt, Dominik; Neumann, Jürgen (Proceedings of the 27th European Conference on Information Systems (ECIS))

He Who Pays the Piper Calls the Tune: Online Review Elicitation by Sellers and Third-Party Platforms in B2B Markets - Neumann, Jürgen; Gutt, Dominik (Proceedings of the 27th European Conference on Information Systems (ECIS))

Do Digital Startups Prepare for Technology Pivots? - An Initial Analysis of Job Adverts - Bohn, Nicolai (Proceedings of the 25th Americas Conference on Information Systems (AMCIS))

Digitale Modellierungen sozialer Räume - Herzig, Bardo; Klar, Tilman-Mathies (Digitale Transformation in der Bildungslandschaft- den analogen Stecker ziehen?)

Service Function Chaining Across OpenStack and Kubernetes Domains - Razzaghi Kouchaksaraei, Hadi; Karl, Holger (13th ACM International Conference on Distributed and Event-based Systems)
Remarkable advantages of Containers (CNs) over Virtual Machines (VMs) such as lower overhead and faster startup has gained the attention of Communication Service Providers (CSPs) as using CNs for providing Virtual Network Functions (VNFs) can save costs while increasing the service agility. However, as it is not feasible to realise all types of VNFs in CNs, the coexistence of VMs and CNs is proposed. To put VMs and CNs together, an orchestration framework that can chain services across distributed and heterogeneous domains is required. To this end, we implemented a framework by extending and consolidating state-of-the-art tools and technologies originated from Network Function Virtualization (NFV), Software-defined Networking (SDN) and cloud computing environments. This framework chains services provisioned across Kubernetes and OpenStack domains. During the demo, we deploy a service consist of CN- and VM-based VNFs to demonstrate different features provided by our framework.
Keywords: Network Function Virtualization; Software-defined Networking; Cloud Computing; service orchestration; OpenStack; Kubernetes